Association between uric acid and height during growth hormone therapy in children with idiopathic short stature - Yoon, Jong Seo; Seo, Young Jun; Kwon, Eun Byul; Lee, Hye Jin; Kang, Min Jae; Hwang, Il Tae (Frontiers in Endocrinology, 2022)
Serum uric acid (UA) within appropriate levels is reported to be beneficial in patients with idiopathic short stature (ISS). This study aimed to evaluate the association between serum UA levels and height standard deviation scores (SDS) in patients with ISS during growth hormone (GH) therapy. A longitudinal study (LG Growth Study) of 182 children (mean age: 7.29±2.60 years) with ISS was performed. All participants were in the prepubertal stage and treated with GH, and the data within a treatment period of 30 months were analyzed. In the adjusted Pearson’s correlation, UA was significantly correlated with height SDS after controlling for sex, age, and body mass index (BMI) SDS (r=0.22, p=0.007). In the adjusted multiple regression analyses, the height SDS was significantly associated with UA after controlling for sex, age, and BMI SDS (β=0.168, p=0.007). Within the 30-month treatment period, the UA levels significantly increased as the height SDS increased, and the mean UA levels at baseline and 30 months after treatment were 3.90±0.64 mg/dL and 4.71±0.77 mg/dL, respectively (p=0.007). In conclusion, UA is related to height SDS, and GH treatment leads to a significant increase in UA without hyperuricemia. Elevated UA is considered a favorable outcome of GH therapy, and further studies are needed to determine its role as a monitoring tool.